Main Pump Seal’s Characteristics Affected by Cone Angle and Clearance - Wang Heshun; Zhu Weibing; Huang Zepei; Zhang Chening (Institute of Advanced Engineering and Science, 2014)
Aimed at the face film characteristics of Main Pump Seal (MPS), related theoretical calculation formulas were deduced based on the Reynolds equation. A case with a certain NPPS is carried out, it is take the leakage as the basic constraint conditions, the calculation focusing on leakage, stiffness and opening force, the end cone angle and clearance change been the main changed parameters. The results show that: (1) Leakage is direct ratio with clearance of three powers;(2) Overall amount of leakage increases with the end cone angle synchronously, and in the smaller cone angle changes significantly while larger slightly; (3) film stiffness increased with clearance (cone angle) first and then decreased, and the maximum value is obtained in a certain clearance (cone angle). Finally, the preferred clearance is preferably in the range of 6 7µm, and the cone angle preferably value is 0.4 2.5'. It is provide a reliable theoretical support for MPS design and key parameter optimization, and conducive to any research related to experiment and application.